Development of a new LC–MS/MS based enzyme activity assay for recombinant urate oxidase in plasma and its application to pharmacokinetics in human - Luo, Xi; Cai, Ning Fang; Cheng, Ze Neng (Journal of pharmaceutical and biomedical analysis, 2013)
•We developed a LC–MS/MS method for the determination of uricase in human plasma.•This assay was based on the detection of specific enzyme reaction product.•This method was applied to a pharmacokinetic study of a new uricase product.•The pharmacokinetic parameters were first obtained in Chinese healthy subjects. A liquid chromatography–tandem mass spectrometry (LC–MS/MS) method was developed and validated for the determination of recombinant urate oxidase in human plasma. This assay was based on the determination of enzyme reaction product, 15N-allantoin, and phenacetin was used as an internal standard (IS). Separation was achieved on a C18 column by the mobile phase of 30% water (containing 0.5% formic acid) and 70% methanol. Quantification was done using multiple reaction monitoring (MRM) mode to monitor the precursor-to-product ion transitions of m/z 161→m/z 118 for 15N-allantoin and m/z 180→m/z 110.1 for IS at positive ionization mode. The calibration curve was established over the range of 2.077–42.06U/l and the correlation coefficient was larger than 0.99. The intra-day and inter-day relative standard deviations were less than 10.6%. Accuracy determined at three concentrations ranged between 98.6% and 109.2%. This method was successfully applied to a pharmacokinetic study of intravenous recombinant urate oxidase produced from Escherichia coli in Chinese healthy volunteers.